THE EFFECTIVENESS OF THE PEOPLE'S BUSINESS CREDIT PROGRAMME IN IMPROVING THE ECONOMIC WELFARE OF THE COMMUNITY: A LITERATUREREVIEW - Rita Hayati; Sudarmo; Imam Syafei (JOURNAL OF COMMUNITY DEDICATION, 2023)
KUR is a government initiative designed to provide access to capital to Micro, Small and Medium Enterprises (MSMEs) in order to encourage inclusive economic growth and job creation. This research uses the literature study method to examine the issue. The results show several important findings. Firstly, KUR has a positive impact on improving community welfare. MSMEs that obtain KUR access are able to increase production capacity, expand market coverage, and create new jobs that directly affect income and living standards. Secondly, there is an imbalance in implementation and benefits between MSMEs in urban and remote areas. More developed areas tend to enjoy greater benefits because they have more access to information and facilities than remote areas. In addition to geographical factors, the quality of MSME management also affects the effectiveness of KUR. MSMEs with better management tend to be more effective in utilising KUR funds for productive activities, while those with poor management have difficulties in optimising the use of these funds. Therefore, it is necessary to increase the access and benefits of KUR evenly across all regions along with management training assistance for MSMEs. In conclusion, KUR is an important tool to improve economic welfare through the empowerment of MSMEs. However, continuous efforts are needed in equalising access, improving the quality of management, and coordinating between stakeholders to maximise the potential benefits of KUR. Thus, this programme can become a significant pioneer in achieving inclusive economic welfare in Indonesia.